2020
DOI: 10.1186/s12889-020-8196-9
|View full text |Cite
|
Sign up to set email alerts
|

“We struggle with the earth everyday”: parents’ perspectives on the capabilities for healthy child growth in haor region of Bangladesh

Abstract: Background Childhood stunting is an important public health problem in the haor region of Bangladesh. Haor areas are located in the north-eastern part of the country and are vulnerable to seasonal flooding. The key objective of this study is to identify the capabilities of the parents and their children that shape multidimensional child growth outcomes in the haor region in the first thousand days of life. Methods A qualitative study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…2 A study by Chakraborthy et al reported in their study that the mothers frequently mentioned the capability to stay healthy and nourished, to stay away from violence, and to practice autonomy in allocating time for child care. 7 The results obtained were the categories of the perception of women on consequences of child violence as Behavioural issues, developmental issues, justifying abuse and few were not aware. A study by Al Odhayani et al, concluded the following results in line with the current study as child abuse is a common problem worldwide, and its physical and psychosocial effects are felt by abused children, their families, and their communities.…”
Section: Discussionmentioning
confidence: 98%
“…2 A study by Chakraborthy et al reported in their study that the mothers frequently mentioned the capability to stay healthy and nourished, to stay away from violence, and to practice autonomy in allocating time for child care. 7 The results obtained were the categories of the perception of women on consequences of child violence as Behavioural issues, developmental issues, justifying abuse and few were not aware. A study by Al Odhayani et al, concluded the following results in line with the current study as child abuse is a common problem worldwide, and its physical and psychosocial effects are felt by abused children, their families, and their communities.…”
Section: Discussionmentioning
confidence: 98%
“…Initially, and as published elsewhere, we identified capabilities for healthy child growth at the child, parental, and household level. A father’s capability to save the lives of mothers and children, expressed as “the capability to save the future” emerged as an important opportunity to secure maternal and child survival [ 24 ]. Maternal and child survival are thus some of the core capabilities for healthy child growth.…”
Section: Methodsmentioning
confidence: 99%
“…In haor areas, lack of resources, extreme weather conditions, and parents’ social norms underlie the high mortality rates both for mothers and their children. Fathers of haor describe their role in achieving a healthy delivery as the capability “to save the future” and identified it as a key dimension of child growth [ 24 ]. In this paper, we focus on this particular paternal capability “to save the future”, using the Capability Framework for Child Growth (CFCG) for its further analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Articles reporting on studies that directly measured capabilities without developing or validating any tools for future use were only found among the qualitative studies and secondary data analyses. Qualitative measurement was performed either by semi-structured interviews [56,57,63,64]…”
Section: Main Aims and Methods Employedmentioning
confidence: 99%
“…The major measurement properties of the different tools are shown in Table 4. Sample sizes among the qualitative and mixed methods approaches varied between n=12 [58] and n=64 [64], while numbers were naturally much larger for the secondary data analyses (between n=2,814 [60] and n=25,180 [59]). Target groups varied widely, from adults in general [23,25,28,57,76], children under the age of two [64], young adults [59] and older adults [24,61,63] to adults with special conditions or characteristics [30-34, 56, 58] For the ICECAP-O, six articles reported on the intended target group of adults over 65 [35,36,40,65,66,71].…”
Section: Measurement Propertiesmentioning
confidence: 99%